Smooth stones from Bible brooks studies, subjects and stories for Christian workers (Kilmarnock, Scotland John Ritchie)
Contents : 1 -- Old Testament : Bright lights in early times 2 -- New Testament : The works and ways of the Lord Jesus 3 -- Bible Studies : From the cross to the crown 4 -- Words of help to soul winners
Keywords: Sermon outlines; Bible study outlines; Lesson outlines; Homiletical illustrations